2013
DOI: 10.1097/qco.0b013e32835c2159
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of bacterial sexually transmitted infections

Abstract: The routine use of genomics in clinical settings is becoming a reality. For STIs, a primary requirement is an understanding of the diversity of circulating strains and how they change over time. This can help to inform future studies and allow us to address real clinical issues such as outbreak identification, global spread of successful clones and antimicrobial resistance monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 79 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…Comparative genomic studies on chlamydia have demonstrated that it undergoes extensive recombination. Genome projects can also help us understand the phenomenon of antibiotic resistance in STD agents, particularly in the cases of C. trachomatis, where very little was known about the genetics of these organisms because of a lack of molecular tools and the inability to grow them outside cell cultures or host organisms [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparative genomic studies on chlamydia have demonstrated that it undergoes extensive recombination. Genome projects can also help us understand the phenomenon of antibiotic resistance in STD agents, particularly in the cases of C. trachomatis, where very little was known about the genetics of these organisms because of a lack of molecular tools and the inability to grow them outside cell cultures or host organisms [14].…”
Section: Discussionmentioning
confidence: 99%
“…Increased usage of nucleic acid amplification tests (NAATs) in the diagnosis of STD leads to the elimination of culture-based techniques, depleting the number of live strains available for resistance testing. A lack of routine test-of-cure makes it impossible to distinguish treatment failure from reinfection [14]. The cost of health care for patients with resistant infections is higher due to longer duration of illness, additional tests and use of more expensive drugs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method enriches for the targeted bacteria in low burden samples and includes an amplification of the target DNA in sufficient quantities suitable for whole-genome sequencing. The method has the advantages of being nonculture based, highly portable and very well suited for de novo sequence assembly The IMS-MDA has been successfully implemented with respect to the obligate intracellular pathogen Chlamydia trachomatis Seth-Smith & Thomson, 2013).…”
Section: Future Directionsmentioning
confidence: 99%